Association between BCG-induced immunity and risk of TB disease - Kagina, Benjamin Mugo (Department of Paediatrics and Child Health, 2015)
We tested the hypothesis that a lower frequency and profile of specific T cells induced by BCG vaccination at birth is associated with subsequent risk of developing tuberculosis.